Timely adoption of Grammarly to cultivate autonomous learning culture - Mariappan, Rajati; Tan, Kim Hua; Philip, Bromeley (Journal of Education and Learning (EduLearn), 2025)
Incorporating technology with linguistics has created opportunities to explore the effectiveness of grammar checkers in cultivating an autonomous learning culture among English as a second language (ESL) and English as a foreign language (EFL) learner. Even though there have been numerous studies on grammar checkers to cultivate autonomous learning culture in higher-education contexts, there are still limited studies in school settings. Thus, this study aims to explore the efficiency of grammar checkers in cultivating an autonomous learning culture among ESL/EFL school students. For this purpose, a qualitative study was conducted, and 13 students aged 16 years from a private Chinese school participated and shared their experiences through a questionnaire. The grammar checker Grammarly has been employed. The findings of this study showed that students found Grammarly easy to use and can correct their writing errors besides improving their grammatical and vocabulary knowledge. Students generally stated that Grammarly helps them to write with less dependence on teachers and helps them to learn the language autonomously. However, 6 out of 13 participants disagreed that Grammarly helps language use. Thus, it is important to know the challenges before employing grammar checkers in the school setting to cultivate an autonomous learning culture.